Impact of the European Payment Index on key macroeconomic and social indicators of a country - Grigonytė, Ingrida; Maknickienė, Nijolė (Business, Management and Economics Engineering, 2014)
The EPI (European Payment Index) reflects the debt risk of corporations in each EU country. This index is widely used for evaluation of the ability of a business to settle with market participants. This article seeks to identify the impact of the EPI on national macroeconomic and social indicators in order to assess the impact made by late payments among business units on the economy of Lithuania. The findings reveal the macroeconomic and social indicators that are most affected by the EPI. Correlation and regression analysis helps to find causal relationships and allows the risks of financial processes in enterprises to be assessed; to reform the national tax system responsibly; and to find appropriate financial instruments to manage late payment threats.